10 nm deep, sub-nanoliter fluidic nanochannels on germanium for attenuated total reflection infrared (ATR-IR) spectroscopy. Issue 2 (30th November 2016) - Sriram, K. K.; Nayak, Simantini; Pengel, Stefanie; Chou, Chia-Fu; Erbe, Andreas
Abstract : Nanoslits with a depth of ∼10 nm were manufactured on a germanium internal reflection element for attenuated internal reflection infrared spectroscopy. Abstract : The fabrication of sub-nanoliter fluidic channels is demonstrated, with merely 10 nm depth on germanium, using conventional semiconductor device fabrication methods and a polymer assisted room-temperature sealing method. As a first application, an ultralow volume (650 pL) was studied by ATR-IR spectroscopy. A detection limit of ∼7.9 × 10 10 molecules of human serum albumin (HSA) (∼0.2 mM) in D2 O was achieved with highly specific ATR-IR spectroscopy.